Implementasi Program Pembinaan Usaha Mikro, Kecil dan Menengah (UMKM) di Kabupaten Kepulauan Meranti - Dian Mir’atun Najah; Weni Puji Hastuti (Al-Manar Journal of Public Administration and Management, 2024)
The purpose of this study was to determine the implementation of the Micro, Small and Medium Enterprises (MSME) coaching program in the Meranti Islands Regency. This research uses a qualitative descriptive approach method which is sourced from primary data and secondary data with 8 resource persons, using interview, observation and documentation research techniques. The results of this study indicate that the coaching carried out by the Meranti Islands Regency Cooperative, UKM and Labor Office has been carried out well, but has not been fully achieved. This is due to budget constraints in carrying out coaching activities for MSMEs and still lack of participation from business actors, lack of minotoring, as well as the lack of comprehensive program socialization for MSMEs and relationships between organizations that are not optimal. In coaching activities, the Office of Cooperatives, SMEs and Manpower of the Kepuluan Meranti Regency needs to provide more guidance, training to MSMEs and carry out routine checks on MSMEs, so that coaching for MSEs is carried out.